Perancangan Fasilitas Fisik Operator SPBU dengan Pendekatan Ergonomi untuk Mengurangi Beban Kerja - Taufiq Rochman; Rahmaniyah Dwi Astuti; Nur Cahyo Saputro (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2010)
This research aims to design chair for helping female operators in performing their work. The design is based on anthropometric measures of 10 female operators. Percentile system is then applied to calculate the chair dimensions so that the chair may be used by operators who have wide range of physical attributes. The design results a chair with five fix legs to maintain its stability. The seat is 41 cm × 39 cm and positioned 57 cm from the floor. The chair has an adjustable lumbar support so that the operator may lie back during the rest time. Both seat and lumbar support are covered with cushion to reduce pressure to the body. The operator can move freely to reach fuel machine and the vehicle without having to turn her body because the chair can rotate 360° horizontally.